Music Therapy for Proactive Wellness - Finnerty, Rachael (My University, 2024)
Support for proactive mental health interventions is imperative to reduce the number of individuals experiencing a mental health crisis. However, proactive mental health interventions are not prioritized within the current healthcare paradigm. It is well established that engaging in proactive measures such as exercise, maintaining good sleep hygiene and adhering to a balanced diet can prevent physical health ailments. Accordingly, proactive management of physical health has become a societal norm. Unfortunately, proactive management of mental health is not societal norm, despite the physical health consequences of poor mental health. Verbal based therapies remain the standard of care within mental health services, and they are primarily available to individuals diagnosed with a mental illness or experiencing a crisis. Due to the stigma associated with verbal-based therapies and seeking mental health support, many individuals are reluctant to proactively seek assistance. In contrast, music is a universally embraced activity, transcending age, ethnicity, socio-economic status and health conditions. The positive associations linked with music may make music therapy a more approachable option for support. In this thesis, I investigated undergraduate university students’ interest in participating in music therapy, as well as the effectiveness of both online and in-person group music therapy as proactive interventions for stress and anxiety. Data were collected from standardized psychometric tools and the physiological markers of heart rate variability and cortisol. The research presented in Chapter 2 of this thesis provides evidence of student interest in music therapy as an option to support mental health. The research presented in Chapter 3 demonstrates the effectiveness of group music therapy as an online intervention for managing stress and anxiety, while Chapter 4 supports the effectiveness of in-person group music therapy for managing stress and anxiety. Together, this research supports the inclusion of music therapy as a cost-effective proactive intervention for stress and anxiety management on university campuses.
Keywords: Music Therapy, Proactive, Wellness, Stress, Anxiety, Cortisol, University Students